The Effects of the COVID-19 Pandemic on the Tourism Industry in Negros Oriental, Philippines - Tayco, Ryan Olindo; Tubog, Millard Vaughn; Rizada, Ma. Leroz P.; Antique, Cynie T.; Zamora, Glennen Y.; Espinosa, Lyra B. (Journal of Business on Hospitality and Tourism, 2023)
The study tries to determine the effects of the pandemic on the tourism industry in Negros Oriental specifically on accommodation facilities and food and beverage establishments. This study is a descriptive method using the correlational technique. The results show that both accommodation facilities and F&B establishments strongly agree that the actions taken during the pandemic are the observance of government protocols. The study also finds out a significant relationship between human resources and operating pressures with actions taken during the pandemic. While for the F&B establishments, human resources, operations, financial situations, operating pressures, and government policies shows a significant relationship to actions taken during the pandemic. It is also said that accommodation facilities that manage by women take action effectively during the pandemic, and accommodations facilities with more employees have more operating pressures compared to businesses with fewer employees. The same can be said with F&B establishments where sex and marital status is significantly related to human resource. This means that F&B establishments managed by single women experienced less effect on their human resources and single women can work effectively during the pandemic.